The Improvement of Civic Virtue through Civic Education in Higher Education in Forming Young Generation Communication Patterns - Lili Halimah; Yayuk Hidayah; Nufikha Ulfah; Risti Aulia Ulfah (research, training and philanthropy institution Natural Aceh, 2021)
This study purposed to describe the communication pattern of students at the University of Ahmad Dahlan Yogyakarta and described Civic Virtue implementation through civic education in higher education in terms of forming young generation communication patterns. This study employed a qualitative descriptive method. The subject of the study was five lecturers of civic education. Data were collected through interviews, observation, documentation, and focus group discussion (FGD). The data were analyzed by using Miles and Huberman’s principles as data reduction, data display, and stating the conclusion. The result of the research showed that the students’ pattern of communication at higher education was influenced by some factors were environment and knowledge factor. The fostering of Civic Virtue through civic education in higher education in forming young generation communication pattern has existed in the process of Civic Virtue fostering that involves democratic values, self-control, and prioritizing plurality interest. The Civic Virtue in the category civic disposition involves responsibility, self-discipline, human rights respect, willingness to hear, negotiating, and compromising. Besides, the Civic Virtue in the category of civic commitment involves a commitment to the implementation of democratic citizenship rights, responsibility for democratic citizenship, constitutionalism, and tendency to participate politically